The night eaters. Book 3, Their kingdom come - Liu, Marjorie M. (Abrams ComicArts, an imprint of Abrams, 2025)
"The thrilling conclusion to the critically acclaimed, award-winning Night Eaters trilogy! What happens when you and your twin accidentally trigger the apocalypse while trying to defend your family from an evil warlock? Well, Milly and Billy are about to find out. Los Angeles has been decimated by the Ting twins and the hole they've accidentally torn in the fabric of the universe. But that's not all . . . across the world things are . . . changing. The long-separated realities of Earth and the magical world have collided with disastrous results. Milly and Billy are desperate to set things straight, but Keon and Ipo know better-some things can't be undone. The final war for the fate of our world has begun. In Their Kingdom Come, the New York Times bestselling creative team Marjorie Liu and Sana Takeda return to conclude their epic tale of magic and monsters, demons and demigods, and the capricious, incontrovertible power of luck."--Publisher's website.